2017
DOI: 10.1111/imj.13557
|View full text |Cite
|
Sign up to set email alerts
|

Impact and implementation of a sustainable regional telestroke network

Abstract: Telestroke was associated with a significant increase in thrombolysis rate and reduction in door-to-needle time in provincial hospitals indicating improved patient care. Quantification of the extra neurologist workload allowed for a seamless transition to 'business as usual' using a novel annual subscription funding and service model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…3,4 Improvement initiatives have included regular audit and review, service model changes to reduce treatment delays, public FAST campaigns to improve community stroke recognition, and the introduction of telestroke in several parts of the country to reduce geographic inequities. 5,6 This article reports on the 2018 New Zealand reperfusion therapy rates, explores the impact of service improvements on temporal trends and geographic variations, and identifies areas requiring further attention to achieve best patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Improvement initiatives have included regular audit and review, service model changes to reduce treatment delays, public FAST campaigns to improve community stroke recognition, and the introduction of telestroke in several parts of the country to reduce geographic inequities. 5,6 This article reports on the 2018 New Zealand reperfusion therapy rates, explores the impact of service improvements on temporal trends and geographic variations, and identifies areas requiring further attention to achieve best patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…National and regional efforts have contributed to increased treatment rates and reduced treatment delays 3,4 . Improvement initiatives have included regular audit and review, service model changes to reduce treatment delays, public FAST campaigns to improve community stroke recognition, and the introduction of telestroke in several parts of the country to reduce geographic inequities 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this study also showed a significant benefit resulting from the more rapid virtual interaction between the patient and the doctor in the hub hospitals in the out-of-hours period. 85 All these data underline the role of modern networking, including telemedicine-based networking, for decreasing critical time delays and improving outcomes in treatment of acute stroke.…”
Section: Telestroke Networkmentioning
confidence: 99%
“…5 Telestroke practices are increasingly considered mature, 6 having shown positive effects on various indicators of quality, including cost savings, access to care, e cacy, patient functional outcomes, and patient satisfaction. 5,7,8 In the United States, most telestroke programs use a hub-and spoke network model, where stroke specialists employed at a full-service hub facility are consulted by limited-service (often rural) spoke facilities. [9][10][11] Some programs serve entire states or multistate regions (e.g., The University of Utah Health's Stroke Center accepts referrals from Utah and six surrounding states).…”
Section: Introductionmentioning
confidence: 99%